PETITE FOURS VARIASI FILLING DAN TOPPING BUAH NANAS SEBAGAI HIDANGAN STAND PESTA - Nisa Rahmaniyah Utami; Fitri Mulyani Saputra (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2021)
Petite fours are small cake dishes, biscuits or various kinds of pastries which are decorated with cooked chocolate, fondant, cream, fruits that are specially decorated, known as bite size or the size of one or two bites. Currently, the party stand dish in the form of petite fours is not widely served because people think that petite fours is an expensive dish. The use of pineapple as a filling or topping on petite fours is rarely found. The purpose of writing is to develop the writer's knowledge and skills in the field of cuisine, especially patisserie, in processing Petite Fours with variations of filling and topping of pineapple as a party stand dish. The method used in this manufacture is an experimental method, namely testing the recipe five times, resulting in petite fours with variations of filling and topping of pineapple as a party stand dish. The party stand dish is the Mini Cake Layers Pineapple.